"Comparisons are Odious?" Revisiting the ancient fable of the ant and the grasshopper adapted in Maugham's short story - Islam, Muhammad Reazul (Journal of English Language and Literature (ISSN: 2368-2132), 2019)
The article seeks to locate a comparative study of the meanings and the morals of a popular ancient fable, adapted by William Somerset Maugham in his short story, The Ant and the Grasshopper. The comparison and contrast in adapting the fable generated an intense academic debate about the appropriate policies of life, a human should undergo. Alike the ancient fable, the setting of the story opens with the conversation between an industrious ant and its reluctant counterpart, a grasshopper. Although the story of the fable is embodied with a moral where industry is rewarded and giddiness punished, we see a completely different scenario at the end of the story. Therefore, it is an irony of the moral conflict between two Ramsay brothers, namely George Ramsay, a man of ethics and Tom Ramsay, a man of a fantasy world. Throughout the story, The Ant and the Grasshopper, Maugham's effort to portray the themes of justice, trust, fear, morality, embarrassment, happiness and struggle is indeed praiseworthy. But, at the same time, it has aroused a hypothesis of seeking out the ultimate principles of life. The paper considers the development of the Greek fable from its origin to the later adaptations, including the version of La Fontaine, a French fabulist, and the final reversal to a counter-fable by Maugham. It also includes a web of researches in the corresponding fields, and a synthesis resulting from the causes and effects of indebtedness and unemployment that can eventually affect the economy through fluctuations in confidence. The further objective of this work illustrates the misconception and mockery of a man of letter and the eventual paradoxes he has to face in reality. Finally, it concludes with an inception that a post modern world like ours needs not only a determined and preset humane policy, but also a new narrative, and liberal outlook to survive or live in luxury.